Is Business Saving Really None of Our Business? - Ricardo N. Bebczuk; Eduardo A. Cavallo (Inter-American Development Bank (IDB), 2014)
This paper investigates the relevance of business saving for private saving and investment around the world by constructing and exploiting a broad international, unbalanced panel of 64 countries over 1990-2012. The paper shows that businesses are the main contributors to private and national saving around the globe, contributing on average more than 50 percent of national saving. Using this unique dataset, evidence is found of partial piercing of the corporate veil: for the core estimation, it is found find that a 1 increase in business saving gives rise to a decrease of only 0. 28 in household saving. The non-neutrality of business saving is further confirmed by results showing that higher business saving is significantly associated with higher business investment. In conjuction with the empirical results, this paper sheds new light on the role of business saving in the economy by critically scrutinizing the existing macroeoconomic and corporate finance literatures.
hdl:11319/6554
Keywords: E21; G32; 330; Business saving; Corporate veil; Domestic saving; Corporate finance